Determination of present-day crustal deformation along the Kenyan rift system using InSAR - Pius Kipng’etich Kirui; Bjorn Riedel; Markus Gerke (Earth, Planets and Space)
Abstract The Kenyan rift system is prone to deformation due to various geological processes and human activities, such as overexploitation of groundwater and exploitation of geothermal energy. Crustal deformation monitoring is essential for understanding the geodynamics of the rift and assessing potential hazards as the rift passes through densely populated areas. However, retrieving InSAR displacement measurements along the Kenya rift system is challenging due to the high variability in tropospheric delay caused by its location in the tropics and the significant topographic variations along the rift. Here, we leverage Sentinel-1 data to analyze both local and large-scale deformation in the rift using multi-temporal InSAR processing with an improved tropospheric correction method, which we previously proposed with a modification on variance covariance modeling. We provide evidence for the previously reported ground displacement of 5 $$-$$ - 7.5 cm southwest of the Suswa volcano as being a misidentification of a tropospheric delay, that was dominant on March 27, 2018. Moreover, we observe episodic ground displacement at Suswa and Longonot, attributable to magma movement. Our results indicate that Suswa experienced a 9 cm movement towards the satellite line of sight between 2018-2020, while Longonot moved 4 cm towards satellite line of sight between 2016-2018 and also underwent 3 cm displacement away from the satellite line of sight between 2019-2021. In addition, we observe land subsidence associated with geothermal exploitation in the range of 1 $$-$$ - 3.6 cm/yr in Olkaria as well as in multiple locations in Nairobi at a rate of up to 6 cm/yr, primarily attributed to groundwater overexploitation. Moreover, we detect undocumented ground displacement at the Chalbi salt flat and along the Elgeiyo escarpment, at rates of up to 4.8 cm/yr and 5.7 cm/yr, respectively. Long-wavelength, low-amplitude deformation at the Turkana depression aligned well with the current kinematics of the Kenyan rift system. We find that localized deformations, caused by magmatism and human activity, dominate the south segment of the rift, whereas large-scale low-amplitude deformations dominate the north segment. In summary, our results emphasize the importance of tropospheric delay correction in retrieving InSAR-derived displacement measurements along the Kenyan rift system. Graphical Abstract